The Impact of Digital Transformation on Small and Medium Enterprises (SMEs) Performance : A Comparative Analysis (Universitas Kristen Indonesia Toraja, 2024)
Digital transformation has significantly influenced the operational efficiency and market competitiveness of Small and Medium Enterprises (SMEs). This study examines the role of digital tools, such as e-commerce platforms and cloud computing, in enhancing SME performance across developing and developed economies. A comparative analysis of case studies from Indonesia and Germany highlights key enablers and barriers to digital adoption, providing actionable insights for policymakers and business leaders.